Additive Ratio Assessment (ARAS) Method in the Selection of Popular Mobile Games - Meidelfi, Dwiny; Idmayanti, Rika; Maulidani, Farhan; Ilham, Muhammad; Muhlis, Farid Alfajr (International Journal of Advanced Science Computing and Engineering, 2022)
Dealing with using smartphones was growing will increase the sales value of the mobile game industry, both from local and foreign developers. It can impact the increasing number of start-ups trying to get involved in the game industry, as well as a large number of job opportunities for those who want to be strengthened in the development of mobile games. This opportunity become the main sector in the domestic creative industry. In Indonesia, the development of mobile games was deemed necessary to analyze the most popular mobile game products that assist by criteria of game. It shows the market trend currently. The researcher hopes this result can provide for developers to choose the type of game to be strengthened based on certain categories. The mobile games involved in this research are Garena Free Fire, Mobile Legend: Bang Bang, PUBG Mobile, Higgs Domino Island, Ragnarok X: Next Generation, Rise of Kingdoms: Lost Crusade, Roblox, State of Survival: Survive The Zombie Apocalypse, Genshin Impact, Coin Monster, Minecraft, Clash Royale, Clash of Clans, Ragnarok M: Eternal Love, State of Survival: The Walking Dead Collaboration. The research was an Additive Ratio Assessment (ARAS) method with the results of 5 recommended mobile games. The test is carried out with a sensitivity test which shows the criterion of "not containing violence" which is the most sensitive criterion among other criteria.